Role of the basal ganglia in the control of sleep and wakefulness - Lazarus, Michael (2013)
The basal ganglia (BG) act as a cohesive functional unit that regulates motor function, habit formation, and reward/addictive behaviors; but the debate has only recently started on how the BG maintain wakefulness and suppress sleep to achieve all these fundamental functions of the BG. Neurotoxic lesioning, pharmacological approaches, and the behavioral analyses of genetically modified animals revealed that the striatum and globus pallidus are important for the control of sleep and wakefulness. Here, we discuss anatomical and molecular mechanisms for sleep-wake regulation in the BG and propose a plausible model in which the nucleus accumbens integrates behavioral processes with wakefulness through adenosine and dopamine receptors.